Efecto del rendimiento en un test máximo incremental sobre la capacidad de salto vertical de árbitros de fútbol. [Effect of maximum incremental test performance on the vertical jump performance in soccer referees]. - Daniel Castillo; Jesús Cámara; Demetrio Lozano; César Berzosa; Silvia Sedano; Javier Yanci (Ramón Cantó Alcaraz, 2019)
Soccer refereeing demand a high neuromuscular implication which it could produce accumulative fatigue and keep down the physical performance of soccer referees. The aims of this study were 1) to describe the performance in an incremental maximum test and in the bilateral and unilateral vertical jump (VJ) capacity in soccer referees, and 2) to analyze the variation on the VJ capacity after performing a maximum incremental test. Before and after performing a cardiovascular incremental test, VJ capacity was measured in 12 high-level soccer referees who officiated at high Spanish competitive-level. On one side, post activation potentiation (PAP) effect was not produced because the improvement of VJ was trivial-small (p > 0,05; ∆ = 0,10-2,19%; d = 0,01-0,21). On the other side, due to the associations between VJ variation and maximum values on the incremental test were small in many cases (r=-0,25/0,24), it could happen that the fatigue induced by the incremental maximum test is not associated to a loss of performance in the vertical jump capacity in high-level soccer referees.